2018
DOI: 10.1111/sltb.12420
|View full text |Cite
|
Sign up to set email alerts
|

Change Pathways in Indigenous and Nonindigenous Youth Suicide

Abstract: Multivariate dynamic relationships among suicide attempts, anxiety and/or depressive symptoms, hope, and help-seeking were examined across time in Native Hawaiian and non-Hawaiian adolescents, using data from a 5-year longitudinal cohort study (N = 7,317). The rate of suicide attempts decreased over time, but this reduction was significantly less among Native Hawaiian youth than their non-Hawaiian peers. There were also significant differences between groups in hope and help-seeking, with Native Hawaiian youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Studies have shown that in Hawaiʻi, a high level of family cohesion, positive friendships, and belonging to a community that enhances connection and care are protective factors against suicide [3,4]. Nevertheless, suicide remains a leading cause of death in are also at a higher risk, with suicide being the second leading cause of death among youth of ages 15-24 and 25-34 years and the fourth leading cause among ages 1 -14, 35-11, and 45-54 years [11].…”
Section: Suicide In Hawaiʻimentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that in Hawaiʻi, a high level of family cohesion, positive friendships, and belonging to a community that enhances connection and care are protective factors against suicide [3,4]. Nevertheless, suicide remains a leading cause of death in are also at a higher risk, with suicide being the second leading cause of death among youth of ages 15-24 and 25-34 years and the fourth leading cause among ages 1 -14, 35-11, and 45-54 years [11].…”
Section: Suicide In Hawaiʻimentioning
confidence: 99%
“…Studies have shown that in Hawaiʻi, a high level of family coh ships, and belonging to a community that enhances connection an factors against suicide [3,4]. Nevertheless, suicide remains a lead Hawaiʻi, with an age-adjusted rate of 12.9 deaths per 100,000 in 2021 [5,6].…”
Section: Suicide In Hawaiʻimentioning
confidence: 99%
See 2 more Smart Citations
“…Local longitudinal research indicated that suicidal ideation, anxiety and parent expectation were the best predictors of suicide attempts for Native Hawaiians and non-Hawaiians with no interaction by ethnic identity (Hishinuma et al, 2017). However, significant differences were found between groups in hope and help-seeking, with Native Hawaiian youth increasing help-seeking and decreasing hope to a greater degree (Goebert, Hamagami, Hishinuma, Chung-Do, & Sugimoto-Matsuda, in press).…”
Section: Native Hawaiian Suicidementioning
confidence: 99%